The Need To Modernize The Mechanisms Of Organizational Management In Family Enterprises - Sultanov, Boburmirzo (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
this article analyzes the current problems of organizational management mechanisms in family enterprises and considers the need and methods of their modernization. Due to the peculiarities of family business, the importance of innovative approaches to improving the effectiveness of management mechanisms, the introduction of digital technologies and the improvement of the management system is emphasized. The article reflects on the role of modern management mechanisms in ensuring the stability of family enterprises and increasing their competitiveness.